Biological clocks and incremental growth line formation in dentine. Issue 2 (7th April 2020) - Papakyrikos, Amanda M.; Arora, Manish; Austin, Christine; Boughner, Julia C.; Capellini, Terence D.; Dingwall, Heather L.; Greba, Quentin; Howland, John G.; Kato, Akiko; Wang, Xiu‐Ping; Smith, Tanya M.
Abstract: Dentine‐ and enamel‐forming cells secrete matrix in consistent rhythmic phases, resulting in the formation of successive microscopic growth lines inside tooth crowns and roots. Experimental studies of various mammals have proven that these lines are laid down in subdaily, daily (circadian), and multidaily rhythms, but it is less clear how these rhythms are initiated and maintained. In 2001, researchers reported that lesioning the so‐called master biological clock, the suprachiasmatic nucleus (SCN), halted daily line formation in rat dentine, whereas subdaily lines persisted. More recently, a key clock gene ( Bmal1 ) expressed in the SCN in a circadian manner was also found to be active in dentine‐ and enamel‐ secretory cells. To probe these potential neurological and local mechanisms for the production of rhythmic lines in teeth, we reexamined the role of the SCN in growth line formation in Wistar rats and investigated the presence of daily lines in Bmal1 knockout mice ( Bmal1 −/− ). In contrast to the results of the 2001 study, we found that both daily and subdaily growth lines persisted in rat dentine after complete or partial SCN lesion in the majority of individuals. In mice, after transfer into constant darkness, daily rhythms continued to manifest as incremental lines in the dentine of each Bmal1 genotype (wild‐type, Bmal +/–, and Bmal1 −/− ). These results affirm that the manifestation of biological rhythms in teeth is a robust phenomenon, imply a more autonomous role of local biological clocks in tooth growth than previously suggested, and underscore the need further to elucidate tissue‐specific circadian biology and its role in incremental line formation. Investigations of this nature will strengthen an invaluable system for determining growth rates and calendar ages from mammalian hard tissues, as well as documenting the early lives of fossil hominins and other primates. Abstract : Rats subject to SCN lesioning maintain incremental rhythms in dentine ranging from daily (5 lines over 5 days from labels 1–2) to subdaily ( 13 lines over 7 days from labels 2–3, followed by 11–12 lines over 4 days from label 3 to sacrifice). Furthermore, the lack of a local rhythmically expressed transcription factor, BMAL1, did not lead to the cessation of daily growth increments in Bmal1 −/− mice after transfer to constant darkness. Biological rhythms in teeth are a robust and enigmatic phenomenon.